(3/5)*e-6=(-2/5)e-3

Simple and best practice solution for (3/5)*e-6=(-2/5)e-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3/5)*e-6=(-2/5)e-3 equation:



(3/5)*e-6=(-2/5)e-3
We move all terms to the left:
(3/5)*e-6-((-2/5)e-3)=0
Domain of the equation: 5)*e!=0
e!=0/1
e!=0
e∈R
Domain of the equation: 5)e-3)!=0
e!=0/1
e!=0
e∈R
We add all the numbers together, and all the variables
(+3/5)*e-((-2/5)e-3)-6=0
We multiply parentheses
3e^2-((-2/5)e-3)-6=0
We multiply all the terms by the denominator
3e^2*5)e-3)-((-6*5)e-3)-2=0
We add all the numbers together, and all the variables
3e^2*5)e-3)-((-30)e-3)-2=0
Wy multiply elements
15e^3-30)e-3)-2=0
We do not support eepression: e^3

See similar equations:

| p+17.12=2.33 | | 70=10(j+2) | | (3/5)*e-6=-2/5e-3 | | -4(s+19)=-12 | | 4d-12=28 | | (3/5)*e-6=-2/5(e-10)-7 | | 5-2+x=2x-3 | | |-w+6|=-7w | | 14u+-10u+-16u=-12 | | 7(x-4)+7=13x-6(x-3) | | 6x-17+48=90 | | p/3+-8=-6 | | 3x+31+2x-6=90 | | t/3-6=2 | | h/3-9=-7 | | (3/5)(e))-6=(-2/5)(e))-3 | | 18+h=36 | | -8=-8(c-90) | | -20+-9n=-92 | | (3/5)(e)-6=(-2/5)(e)-3 | | -j+4=-3 | | 4x+8x-42=105-9x | | f/7+56=47 | | 5.8=-4.5+x | | 3k-2=-2|k+2| | | 6-5s/3=s | | g/7-6=1 | | 5r-1=14 | | 4e+12=-e+7 | | (3/5*e)-6=)=(-2/5e)-3 | | 80=2(d-10) | | 3(x-2)=-5x+12-x |

Equations solver categories